A Comparison Between Virtual Patient and Peer-Assisted Learning in Teaching Basic Medical Knowledge and Skills. (2020) - Seifert, Lukas; Manap, Arda; Sterz, Jasmina; Gerlach, Ferdinand; Sader, Robert
No abstract available